Climate change impacts on the vegetation carbon cycle of the Iberian Peninsula - Intercomparison of CMIP5 results - Aparício, Sara (2018)
The vulnerability of a water-limited region like the Iberian Peninsula (IP) to climate changes drives a great concern and interest in understanding its impacts on the carbon cycle, namely, in terms of biomass production. This study assesses the effects of climate change and rising CO2 on forest growth, carbon sequestration, and water-use efficiency on the IP by late 21st century using 12 models from the CMIP5 project (Coupled Model Intercomparison Project Phase 5). We find a strong agreement among the models under representative concentration pathway 4.5 (RCP4.5) scenario, mostly regarding projected forest growth and increased primary production (13, 9% of gross primary production (GPP) increase projected by the models ensemble). Under RCP8.5 scenario, the results are less conclusive, as seven models project both GPP and net primary production to increase (up to 83% and 69%, respectively), while the remaining four models project the IP as a potential carbon source by late century. Divergences in carbon mass in wood predictions could be attributed to model structures, such as the N cycle, land model component, land cover data and parameterization, and distinct clusters of Earth System Models (ESMs). ESMs divergences in carbon feedbacks are likely being highly impacted by parameterization divergences and susceptibility to climate change and CO2 fertilization effect. Despite projected rainfall reductions, we observe a strong agreement between models regarding the increase of water-use efficiency (by 21% and 34%) under RCP4.5 and RCP8.5, respectively. Results suggest that rising CO2 has the potential to partially alleviate the adverse effects of drought.